Ocular Manifestations and Risk Factors of HIV in a Single-Center Observational Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Rosa, Havilah Zeki; Havriza Vitresia (HM Publisher, 2024)
Background: Human immunodeficiency virus (HIV) infection is associated with various ocular manifestations, impacting visual health and quality of life. This study aimed to investigate the spectrum of ocular manifestations and their associated risk factors in HIV-positive individuals at Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: This single-center observational study included HIV-positive patients presenting with ocular complaints at Dr. M. Djamil General Hospital between 2019 and 2021. Comprehensive ophthalmic examinations were conducted, and data on demographics, HIV disease stage, CD4+ T-cell count, antiretroviral therapy (ART) status, and ocular findings were collected. Statistical analysis was performed to identify associations between risk factors and specific ocular manifestations. Results: A total of 149 HIV-positive patients were included in the study, with 7 (4.7%) presenting with ocular manifestations. The most common ocular manifestation was cytomegalovirus (CMV) retinitis (57.1%), followed by retinal nerve fiber layer (RNFL) thinning (42.9%). Other manifestations included visual field disturbances and herpes zoster ophthalmicus (HZO). Low CD4+ T-cell count (<200 cells/μL) was significantly associated with CMV retinitis (p < 0.05). Conclusion: CMV retinitis and RNFL thinning were the predominant ocular manifestations in this HIV-positive cohort. Low CD4+ T-cell count emerged as a significant risk factor for CMV retinitis. Early detection and prompt management of ocular manifestations are crucial to prevent visual impairment in HIV-positive individuals.